Health Technology Assessment untuk Alat Kesehatan: Scoping Review - Fatmawati; Izzati Muhimmah; Rahadian Kurniawan (Jurnal Kesehatan Komunitas, 2022)
Prior to the implementation of health technology, the proposed system or device needs to be assessed in various aspects. This assessment is known as the Health Technology Assessment (HTA). HTA is a systematic evaluation on effect, and/or impact of health technology which aims to provide information to policy makers regarding health technology. This information is needed to minimize costs and prevent the adoption of questionable technologies. The health technology in question can be in the form of drugs, therapy, medical procedures, and medical devices. The HTA process and methodology for medicines has been widely used, while for medical devices it is still scarce. From several literature reviews, the use of HTA criteria is different even though the nature of the object under reviews was in the same category of medical device. Hence, we conducted a study to determine what criteria that are often used in HTA for medical devices. The method in this research was a scoping review on previous HTA publications (n=392) available on PubMed and ScienceDirect databases. Based on the results of a literature search using PRISMA, there were only 7 articles according to the inclusion criteria related to HTA for medical devices with different subjects, namely: medical devices and hospital based HTA. Conclusion from these findings, it can be learned that the criteria often used in HTA for medical devices were namely economy, safety, effectiveness, and organization.